Is Psychological Stress a Factor for Incorporation Into Future Closed-Loop Systems?. (May 2016) - Gonder-Frederick, Linda A.; Grabman, Jesse H.; Kovatchev, Boris; Brown, Sue A.; Patek, Stephen; Basu, Ananda; Pinsker, Jordan E.; Kudva, Yogish C.; Wakeman, Christian A.; Dassau, Eyal; Cobelli, Claudio; Zisser, Howard C.; et al.
Background: The relationship between daily psychological stress and BG fluctuations in type 1 diabetes (T1DM) is unclear. More research is needed to determine if stress-related BG changes should be considered in glucose control algorithms. This study in the usual free-living environment examined relationships among routine daily stressors and BG profile measures generated from CGM readings. Methods: A total of 33 participants with T1DM on insulin pumps wore a CGM device for 1 week and recorded daily ratings of psychological stress, carbohydrates, and insulin boluses. Results: Within-subjects ANCOVAs found a significant relationship between daily stress and indices of BG variability/instability ( r = .172 to .185, P = .011 to .018, r 2 = 2.97% to 3.43%), increased % time in hypoglycemia ( r = .153, P = .036, r 2 = 2.33%) and decreased carbohydrate consumption ( r = –.157, P = .031, r 2 = 2.47%). Models accounted for more variance for individuals reporting the highest daily stress. There was no relationship between stress and mean daily glucose or low/high glucose risk indices. Conclusions: These preliminary findings suggest that naturally occurring daily stressors can be associated with increased glucose instability and hypoglycemia, as well as decreased food consumption. In addition, findings support the hypothesis that some individuals are more metabolically reactive to stress. More rigorous studies using CGM technology are needed to understand whether the impact of daily stress on BG is clinically meaningful and if it is a behavioral factor that should be considered in glucose control systems for some individuals.